Určení geotechnických a geologických charakteristik vybraných zemin a stanovení jejich vhodnosti pro zakládání staveb v Lískovci u Koryčan - Králík, Michal (Vysoké učení technické v Brně. Fakulta stavební, 2016)
Cílem bakalářské práce je zhodnotit vlastnosti zeminy v dané lokalitě Českého masívu jako základovou půdu. Průzkum se zabývá geomechanickými vlastnostmi, v rámci možností i vlastnostmi hydrogeologickými. První úkol je rešeršní činnost studované lokality, následuje průzkumná činnost, při které získáme vzorky, které analyzujeme v laboratoři a na základě těchto výsledků navrhneme vhodný způsob založení.

Aim of this bachelor thesis is determination characteristics of soil from selected location in Czech Massif and determine its sustainbility for foundation construcion, survey is aimed at geotechnical characteristics but also hydrological characteristics if underground water will be reached. First objective is search activities of geology destription in selected location followed by survey activities and taking soil samples, which we analyze in laboratory and we suggest appropriate type of founding construction based on results.
Determination of geotechnical and geological characteristic of soils and evaluation of their suitability for building construction in Koryčany-Lískovec
Keywords: Geologie; geomechanika; geotechnický průzkum; laboratoř mechaniky zemin; Geology; geomechanics; geological survey; laboratory of soil mechanics